Parameter optimization of the controller for a half car active suspension system [electronic resource] - 432597 Abdul Hamid -A- Abo Hagar (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan Elektrik (Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2008